Effects of supplemental nanoparticle trivalent chromium on the nutrient utilization, growth performance and serum traits of broilers. Issue 1 (20th June 2014) - Lin, Y. C.; Huang, J. T.; Li, M. Z.; Cheng, C. Y.; Lien, T. F.
Summary: The aim of this study was to investigate the effect of dietary supplementation of nanoparticle trivalent chromium on nutrient utilization, growth performance and serum traits of broilers. This study included two trials. In trial 1, 32 three‐week‐old broilers were divided into four groups: the control, chromium chloride (CrCl3 ), chromium picolinate (CrPic) and nanoparticle chromium picolinate (NanoCrPic). Chromium was added at a 1200  μ g/kg level to evaluate the nutrient and chromium utilization. In trial 2, 160 one‐day‐old broilers were randomly divided into four groups as in trial 1, with four replicates. The results of trial 1 indicated that the chromium utilization is as follows: NanoCrPic > CrPic > CrCl3 and control groups, with significant differences between groups (p < 0.05). Crude fat utilization in CrCl3 group was lower than in that the control group (p < 0.05). The results of trial 2 indicated that feed intake of 4–5 weeks showed better result in the CrCl3 group than that in the CrPic group (p < 0.05). The results of serum traits indicated that the LDL‐cholesterol in the NanoCrPic groups was lower than that in the CrPic group (p < 0.05). The NanoCrpic and CrPic groups showed significantly increased serum chromium concentration when compared with the control and CrCl3 groups; the triglyceride level in the CrCl3 group was lower than that in the CrPic group (p < 0.05). This study concluded that compared with CrPic, NanoCrpic supplementation could increase chromium utilization and lower the serum LDL‐cholesterol of broilers.